Pengaruh Bargaining Power Perempuan terhadap Partisipasi Kerja Perempuan Menikah di Provinsi Bali (Lembaga Pengembangan Kinerja Dosen, 2026)
The majority of married women are still concentrated in the informal sector, indicating limited employment options. The province of Bali places married women with significant customary and domestic responsibilities. The fact that there are differences in labor participation patterns based on education level raises the suspicion that education not only plays a role in human capital but also as a resource that strengthens women's bargaining power in the negotiation process of household decision-making amidst the strong role of customary and domestic roles that often place women in a weak bargaining position. Using data from the 2023 National Socioeconomic Survey (Susenas), this study aims to analyze women's bargaining power, as measured by the wife's education, on the labor participation of married women in Bali Province, with control variables of husband's education, age, number of children, and area of ​​residence. An ordered logit analysis shows that women's education as a measure of bargaining power significantly influences married women's labor participation, with women with higher levels of education having a greater tendency to work in the formal sector. This finding confirms that married women's labor participation is a result of the negotiation process within the household. Therefore, women's employment policies need to consider strengthening women's bargaining power, particularly through increasing access to education.